Analisis Akuntabilitas Pengelolaan Anggaran Pada Markas Palang Merah Indonesia (PMI) Provinsi Gorontalo - Rahmatia Rahmatia (Tasharruf: Journal Economics and Business of Islam, 2019)
This research airms to understand and analyze the responsibility of budget management on the quarter of Indonesian Red Cross Society in Gorontalo Province. This research used descriptive methodology within qualitative approach. There are 12 informants of this research, they are the headquarter as the policy taker of Indonesian Red Cross Society, administrative division, service division, finance division as well as the society. The result and discussion of this research showed that the overall budget management of Indonesian Red Cross Society in Gorontalo Province were responsibility handled according to the regulations and provisons which are applicable on Indonesian Red Cross Society. But there are some rules of the Article of Associations and Bylaws that aren’t be done by Indonesian Red Cross Society in Gorontalo Province, it’s concerning to the source of the fund of Indonesian Red Cross Society that according to the article of associations and bylaws chapter XX article 70 which are from the grant of government, support from International Red Cross Society and the other organizations, donations, another business, funding fees, and month of funds.Penelitian ini bertujuan untuk mengetahui dan menganalisis akuntabilitas pengelolaan anggaranpada Markas Palang Merah Indonesia (PMI) Provinsi Gorontalo.Penelitian ini menggunakan metodologi penelitian deskriptif dengan pendekatan kualitatif.Adapun Informan dalam penelitian ini berjumlah dua belas (12) orang yang meliputi kepala markas PMI selaku pengambil kebijakan di markas PMI, bidang administrasi, bidang pelayanan, bidang keuangan, serta masyarakat.Hasil penelitian dan pembahasan menunjukkan bahwa secara keseluruhan penyelenggaraan pengelolaan anggaran pada PMI Provinsi Gorontalo telah akuntabel sesuai dengan peraturan dan ketentuan yang berlaku pada PMI. Akan tetapi ada beberapa peraturan AD/ART yang tidak dilakukan oleh  PMI Provinsi Gorontalo. Yakni mengenai Sumber dana PMI yang menurut AD/ART BAB XX Pasal 70 berasal dari bantuan hibah pemerintah, bantuan dari Gerakan Internasional Palang Merah dan Organisasi lainnya, sumbangan dan usaha lain yang tidak mengikat, iuran dana, dan bulan dana.